Comparative utilization of urea and fungal treated mustard straw by sheep - MISHRA, A S; CHATURVEDI, O H; MISRA, A K; KARIM, S A (The Indian Journal of Animal Sciences, 2014)
The present study was conducted to detennine relative efficacy of urea and fungal treated mustard straw in maintainingadult sheep. Mustard straw (MS) treated with urea (UTMS) and fungus (FTMS) was fed ad lib. to ewes in G1 and (i) respectively, along with 200 g concentrate mixture/head/day. Urea treatment ofMS increased its CP content from 3.7 to7.2% which further increased to 7.7% in FTMS. Hemicellulose and cellulose content decreased with proportionate increasein NDF and ADF in UTMS while the cell wall constituents further decreased in FTMS. Daily DMI in unit body weight ormetabolic body size was higher (P